Fluoride Varnishes for Preventing Occlusal Dental Caries: A Review - Baik, Alaa (Dent J (Basel), 2021)
Dental caries are most likely to occur on occlusal surfaces from the early eruptive stages of the tooth. In children, about 80% to 90% of dental caries are occlusal caries. Different preventive modalities are used to prevent occlusal caries. One of the methods used for occlusal caries prevention is fluoride varnish. A vast number of clinical trials have evaluated several types of sealant material and fluoride varnish to assess their ability to prevent occlusal caries in both primary and permanent dentition. The purpose of the current study was to provide an updated overview of the development, composition, mechanism of action, application, and safety of fluoride varnish, as well as its effect on occlusal caries prevention. This review of recently published studies on fluoride varnish and its effect on occlusal caries prevention shows that in children at moderate to high risk of caries, fluoride varnishes prevent occlusal caries. Both resin-based fissure sealants and fluoride varnish are effective for occlusal caries prevention for first-permanent molars. However, it was not possible to identify which one has the best effect. It is recommend that fluoride varnish is applied for children at high risk of caries two to four times per year.